The relationship between smoking dose with oxygen saturation and cardiorespiratory endurance on young adult men - Ida Ayu Astiti Suadnyana; Ni Luh Gede Aris Maytadewi Negara; I Wayan Wiraguna (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Healthy lifestyle can reduce the risk of disease. One of the unhealthy lifestyle patterns is consuming cigarettes. Smoking can also reduce the affinity of oxygen for hemoglobin so that it can affect oxygen saturation levels in the blood. This study aimed to determine the relationship between smoking dose, oxygen saturation, and cardiorespiratory endurance in adult men. Methods: The study design was a cross-sectional study with an adult male population in the Tampaksiring Village, Bali, Indonesia, in which they qualified for the inclusion and exclusion criteria. Adult men were selected by purposive sampling. It was obtained 52 samples. The measurement of smoking dose using the Brinkman index, the measurement of oxygen saturation using oximetry, and the measurement of cardiorespiratory endurance using the Harvard step test. Data were analyzed using computer software with the Spearman rank test to determine the relationship between smoking dose with oxygen saturation and cardiorespiratory endurance in adult men. Results: The results showed that from 52 adult men were obtained by analysis result of the relationship between smoking dose and oxygen saturation where p= 0.000 (p<0.05) and the analysis result of the relationship between smoking dose and cardiorespiratory endurance with p= 0.000 (p<0.05). Conclusion: There was a significant relationship between smoking dose with oxygen saturation and cardiorespiratory endurance in adult men in Tampaksiring Village, Bali, Indonesia